The Role of Village Savings and Loan Associations in Poverty Graduation Programs: A Process Analysis - Abdel Hamid, Noha (AUC Knowledge Fountain, 2022)
Ten percent of the global population live in extreme poverty under $1.90 a day. To combat chronic multidimensional poverty, the Bangladesh Rural Advancement Committee (BRAC)created the Graduation Approach, which consists of a Big Push effect implemented through a series of interventions including asset transfer, mentoring, saving groups and a series of service provisions, to push ultra-poor households to exit poverty sustainably. Implemented so far in over 50 countries, the model has shown positive results even after ten years of the first interventions. Sawiris Foundation for Social Development partnered with BRAC and the Abdul Latif Jameel Poverty Action Laboratory (J-PAL) to implement the program in Egypt, starting in 2018, called Bab Amal. I am looking at the model and focusing on the saving groups and their effectiveness and comparing them to the current Village Saving and Loan Associations (VSLA) methodology, implemented by multiple NGOs, and currently adopted by the Egyptian government to scale on a national level. The methodology is based on qualitative research informed by semi structured in depth interviews and focus group discussions with the participants of the program in Assiut and Sohag. The analysis shows that the graduation approach adopted in Bab Amal, including the saving groups component, has contributed to increasing savings, creating income generating activities, improving communication and decision-making abilities within the household and the group and empowering women socially and economically. The program also raised awareness on issues of hygiene, health, education, life skills, gender-based violence and drug addiction. The study also shows very limited borrowing activities which may risk the sustainability of the model in the growth phase of the enterprises. From a process analysis perspective, it is recommended to adopt the VSLA model instead of regular saving groups, as it operates from a bottom-up approach that creates improved abilities for borrowing, improved governance and ownership of the model, all essential for growth and sustainability. The nature of Bab Amal as a pilot and the randomized selection of households it adopted, could not allow the self-selection of the saving groups, which had smaller groups, inefficient for the borrowing activity that is essential for sustainability beyond the project life.